Escore de cálcio coronário na estratificação do risco cardiovascular de portadores de HIV/AIDS em tratamento - Burgos, Ursula Maria Moreira Costa (2019)
Background. Nearly 37 million people living with the human immunodeficiency virus (HIV) and antiretroviral treatment have allowed the disease to become chronic, leading to the association of other conditions such as coronary artery disease (CAD). The use of the Coronary Artery Calcium Score (CACs) in this scenario may add information to risk stratification for CAD. Objectives. To evaluate HIV-positive patients by using CACs, compare it with that of patients without HIV and to evaluate factors associated with pathological CACs. Methods. Ninety-seven HIV/AIDS patients from the Infectious Diseases Outpatient Clinics of the University Hospital of the Federal University of Sergipe and the Sergipe Center for Medical Specialties were included in the study. They underwent a clinical and laboratory evaluation and coronary tomography for CACs evaluation. This sample was compared with a control group (composed of a seronegative patients database without previous cardiovascular disease). Results. Individuals with HIV / AIDS had a mean age of 46.9 ± 11.4 years vs. 55.5 ± 14.8 years in the control group (p <0.001) as well as had less hypertension (20.2% vs. 50.4 %; p <0.001) and diabetes (5.3% vs. 23.3%; p <0.001) than those not infected with HIV. On the other hand, both groups have the same EC level. In the adjusted odds ratio age (OR = 1.08; 95% CI = 0.98-1.17; p = 0.006), male gender (OR = 3.61; 95% CI = 1.06-12.30; p = 0.041) and use of protease inhibitors (PI) (OR = 3.38; 95% CI = 1.10-10.40; p = 0.033) are factors associated with coronary calcification. Most patients with HIV have undetectable viremia and high CD4 + counts, along with lipid profile disorders (total cholesterol> 200 mg / dl = 34.0 %, LDL cholesterol> 130 mg / dl = 28.9% and triglycerides > 150 mg / dl = 37.1%). Conclusion. Our findings suggest that HIV/AIDS and / or its treatment predisposes to coronary calcification, since even younger and with less classical risk factors, patients with HIV/AIDS have the same degree of coronary calcification as seronegative ones, being factors related to a higher chance of calcification age, male gender and PI use.